Microbial network, phylogenetic diversity and community membership in the active layer across a permafrost thaw gradient - Rhiannon Mondav; Carmody K. McCalley; Suzanne B. Hodgkins; Steve Frolking; Scott R. Saleska; Virginia I. Rich; Jeff P. Chanton; Patrick M. Crill (Environmental Microbiology, 2017)
Summary Biogenic production and release of methane (CH 4 ) from thawing permafrost has the potential to be a strong source of radiative forcing. We investigated changes in the active layer microbial community of three sites representative of distinct permafrost thaw stages at a palsa mire in northern Sweden. The palsa site (intact permafrost and low radiative forcing signature) had a phylogenetically clustered community dominated by Acidobacteria and Proteobacteria . The bog (thawing permafrost and low radiative forcing signature) had lower alpha diversity and midrange phylogenetic clustering, characteristic of ecosystem disturbance affecting habitat filtering. Hydrogenotrophic methanogens and Acidobacteria dominated the bog shifting from palsa‐like to fen‐like at the waterline. The fen (no underlying permafrost, high radiative forcing signature) had the highest alpha, beta and phylogenetic diversity, was dominated by Proteobacteria and Euryarchaeota and was significantly enriched in methanogens. The Mire microbial network was modular with module cores consisting of clusters of Acidobacteria , Euryarchaeota or Xanthomonodales . Loss of underlying permafrost with associated hydrological shifts correlated to changes in microbial composition, alpha, beta and phylogenetic diversity associated with a higher radiative forcing signature. These results support the complex role of microbial interactions in mediating carbon budget changes and climate feedback in response to climate forcing.